Dielectric and ferroelectric properties of the graphene doped hydroxyapatite ceramics - Hendi, A. A.; Yakuphanoğlu, Fahrettin (Elsevier, 2020)
Graphene-doped hydroxyapatite ceramics were synthesized by the hydrothermal method. The structural properties of the samples were analyzed by SEM, EDS, XRD and FTIR techniques. The hydroxyapatite was formed from the nanoparticles with sizes of 25 nm-115 nm and the size of it is controlled by the graphene doping. The ferroelectric properties of graphene doped HaP ceramics were analyzed with respect to graphene doping ratios. The ceramics samples exhibited a ferroelectric behavior. It is evaluated that the graphene doped hydroxyapatite materials can be used in biotechnological applications. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Ferroelectric; Ceramics; Graphene; Hydrothermal method